An image-guided robot system for direct cochlear access. (May 2014) - Bell, Brett; Williamson, Tom; Gerber, Nicolas; Gavaghan, Kate; Wimmer, Wilhelm; Kompis, Martin; Weber, Stefan; Caversaccio, Marco
<x content-type="archive" xml:space="preserve">Abstract</x> The aim of direct cochlear access (DCA) is to replace the standard mastoidectomy with a small diameter tunnel from the lateral bone surface to the cochlea for electrode array insertion. In contrast to previous attempts, the approach described in this work not only achieves an unprecedented high accuracy, but also contains several safety sub-systems. This paper provides a brief description of the system components, and summarizes accuracy results using the system in a cadaver model over the past two years.